Impact of the Joint Advisory Group on Gastrointestinal Endoscopy (JAG) on endoscopy services in the UK and beyond. Issue 2 (13th November 2018) - Siau, Keith; Green, John T; Hawkes, Neil D; Broughton, Raphael; Feeney, Mark; Dunckley, Paul; Barton, John Roger; Stebbing, John; Thomas-Gibson, Siwan
Abstract : The Joint Advisory Group on Gastrointestinal Endoscopy (JAG) was initially established in 1994 to standardise endoscopy training across specialties. Over the last two decades, the position of JAG has evolved to meet its current role of quality assuring all aspects of endoscopy in the UK to provide the highest quality, patient-centred care. Drivers such as changes to healthcare agenda, national audits, advances in research and technology and the advent of population-based cancer screening have underpinned this shift in priority. Over this period, JAG has spearheaded various quality assurance initiatives with support from national stakeholders. These have led to the achievement of notable milestones in endoscopy quality assurance, particularly in the three major areas of: (1) endoscopy training, (2) accreditation of endoscopy services (including the Global Rating Scale), and (3) accreditation of screening endoscopists. These developments have changed the landscape of UK practice, serving as a model to promote excellence in endoscopy. This review provides a summary of JAG initiatives and assesses the impact of JAG on training and endoscopy services within the UK and beyond.